What is governance in global telecoupling? - Newig, Jens; Lenschow, Andrea; Challies, Edward; Cotta, Benedetta; Schilling-Vacaflor, Almut (Ecology and Society, 2019)
The concept of telecoupling is increasingly used as a framework to understand globally distant interconnections and their sustainability implications. Although there is a growing research focus on issues of governance related to global telecoupling, there appears little consensus over the meaning of “governance” in this respect. Papers in the recent Ecology and Society special feature titled “Telecoupling: A New Frontier for Global Sustainability” reveal quite different understandings of the telecoupling-governance relationship. We want to suggest that greater clarity and a common understanding of how governance figures in telecoupled systems will aid constructive dialogue on how to govern telecoupling toward more sustainable pathways in the face of pressing global social and environmental issues. This response, though not aiming to define a single, definitive framework of governance as it pertains to telecoupling, seeks to identify three distinct perspectives applied to governance in the context of global telecoupling: (1) governance by states or other actors that induces or fosters telecoupling in the first place, often irrespective of its sustainability implications; (2) governance mainly by private companies that coordinates telecoupled flows; and (3) governance by states, nonstate actors, and hybrid or multistakeholder initiatives that aims to address the negative externalities of telecoupling. By distinguishing these perspectives, we aim to make underlying understandings of governance explicit, and to foster further constructive exchange on the topic.
CRIS-Team Scopus Importer:2023-11-20
Keywords: Global commodity chains; Global environmental governance; Inter-regional connectedness; Sustainability governance